2012
DOI: 10.1007/s11062-012-9235-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxytocin on the Emotional State and Behavior of Rats under Stress Conditions

Abstract: Oxytocin, a hormone exerting controlling effects on lactation, sexual and maternal behavior, and cyclic organization of sleep and wakefulness, is capable of significantly modulating reactions of the organism to the action of stressogenic stimuli. We studied the effects of injections of synthetic oxytocin on the behavioral phenomena and emotional state of rats during realization of a proconflict test induced by "punishments" (nociceptive electrical stimuli) in the process of drinking after water deprivation. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…Oxytocin (OT) has recently received attention as a positive indicator of pleasure of livestock, one of the most important aspects of animal welfare ( Broom and Fraser, 2007 ). It was reported that OT injections after a stress test induced normalization of the emotional state in rats ( Svanidze et al, 2012 ). In humans, OT reduced activation of the amygdala, a central component of fear neurocircuity ( Kirsch et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Oxytocin (OT) has recently received attention as a positive indicator of pleasure of livestock, one of the most important aspects of animal welfare ( Broom and Fraser, 2007 ). It was reported that OT injections after a stress test induced normalization of the emotional state in rats ( Svanidze et al, 2012 ). In humans, OT reduced activation of the amygdala, a central component of fear neurocircuity ( Kirsch et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Increased stress responses were recorded in mice lacking the OXT gene during maze exploration [36] and a similar result was observed after intranasal OXT administration during a social isolation test in ewes [37]. OXT mediates the stress responses in the presence of social partners (social buffering) [38]; also, synthetic OXT administration helps to normalize the emotional state from a stressful event, favoring the recovery of normal behaviors [39]. It has been hypothesized that OXT may cause endocrine changes in the activity of the hypothalamus-pituitary-adrenal axis by acting as a key modulator of anxiety-related behaviors (reviewed in [40]) and several studies have reported the involvement of OXT in the control of social stress by reducing the cortisol response [41][42][43][44].…”
Section: Introductionmentioning
confidence: 61%
“…These results are supported by those of Dhakar et al [ 24 ], who showed that OT-receptor knockout rats performed exhibited aggressive behavior than intact animals. Further, centrally administered OT also induced grooming behavior in male rats [ 25 ], affiliative response of huddled sitting in the subordinate squirrel monkey [ 26 ], and flexible behaviors such as locomotors activity in the open field under stress condition [ 27 ].…”
Section: Roles Of Oxytocin On Animal Welfarementioning
confidence: 99%